HYPOTHETICAL PORTFOLIO FORMULARIZATION OF FINANCIAL ASSETS USING THE TECHNIQUE MULTIVARIATE ANALYSIS OF CLUSTERS - Silva, Wesley Vieira da (2009)
The objective this paper is to identify groups of stocks with similar characteristics (hypothetical portfolio), having as a goal the allocation of capital available for investment so as to understand the potential risks and possible returns that a potential investor could have. Therefore, cluster analysis technique was used on stocks traded at the São Paulo Stock Exchange. The period analyzed was from 1998 to 2002 for the construction of the clusters, and from 2002 to 2006 for the evaluation of the behavior of the portfolios originated from the cluster analysis. Five hypothetical portfolios were identified, being three of them considered suitable for a potential investor, as follows: Portfolio 1 – low risk, low return; Portfolio 3 – low risk, high return; and Portfolio 5: high risk, high return. The behavior evaluation of the suggested hypothetical portfolios showed the expected performance within the period from 2002 through 2006, proving the adequation of the cluster analysis technique. Nevertheless, despite the observed results, it is emphasized that a conjunctural analysis associated with mathematical and (or) econometric studies is essential to the construction of good investment portfolios.